Risk-behaviour screening for identifying adolescents with mental health problems in Europe - Kaess, Michael; Brunner, Romuald; Parzer, Peter; Resch, Franz (European child & adolescent psychiatry, 2014)
Indicated prevention of mental illness is an important public health concern among youth. The aim of this study was to establish a European school-based professional screening among adolescents, which included variables on both a broad range of risk-behaviours and psychopathology; and to investigate the indicative value of adolescent risk-behaviour and self-reported psychopathology on help-seeking and psychological problems that required subsequent mental healthcare. A two-stage professional screening approach was developed and performed within the multi-centre study “Saving and Empowering Young Lives in Europe” (SEYLE). The first stage of screening comprised a self-report questionnaire on a representative sample of 3,070 adolescents from 11 European countries. In the second stage, students deemed at-risk for mental health problems were evaluated using a semi-structured clinical interview performed by healthcare professionals. 61 % of participants (n = 1,865) were identified as being at-risk in stage one. In stage two, 384 participants (12.5 % of the original sample) were found to require subsequent mental healthcare during semi-structured, clinical assessment. Among those, 18.5 % of pupils were identified due to screening for psychopathology alone; 29.4 % due to screening for risk-behaviours alone; and 52.1 % by a combination of both. Young age and peer victimization increased help-seeking, while very low body mass index, depression, suicidal behaviour and substance abuse were the best predictors of referral to mental healthcare. Screening of risk-behaviours significantly increased the number of detected students requiring subsequent mental healthcare. Screening of risk-behaviours added significant value in identifying the significant amount of European pupils with mental health problems. Therefore, attention to adolescent risk-behaviours in addition to psychopathology is critical in facilitating prevention and early intervention. Identifying factors that increase compliance to clinical interviews are crucial in improving screening procedures.